Distributed Virtual Reality Environments Over Web for Distance Education - Christos Bouras; A Philopoulos (EDEN Conference, Bologna, Italy, 1998)
Virtual Environments for education have been discussed in various ways. While advanced multi-user educational VEs are still speculation, simpler VEs based on standard technologies have been in existence for some time. On the other hand, there is a great enthusiasm for promoting Virtual Reality as a major factor in future (and present) environments for training and education. In this paper, we discuss the concept of the Distributed Virtual Environments and the use of them in distance education applications. Next, we consider VRML technology as the key technology for building such environments and we present the basic features and functionalities of it that make it suitable for delivering VEs over the Web. In addition to this, we present some of the roles of VRML in education. Finally, we conclude with some recommendations on the construction of Virtual Reality Environments for educational purposes.